A structural analysis of the infidelity-themed movies in the Philippines - Molinos, Jahzeel Sally P.
A structural analysis of the infidelity-themed movies in the Philippines is an analysis discussing the growing mistress-themed phenomenon in the Philippine cinema. Six films were used in this study shown from 2011 to May 2013: My Neighbor?s Wife (2011), No Other Woman (2012), The Mistress (2012), A Secret Affair (2012), Seduction (2013) and the Bride and the Lover (2013). This study aims to identify and analyse the similarities and differences in structural patterns composing the six films; presentation of each character (legal wife/girlfriend, legal husband/boyfriend, and the third party); and to determine how these six films define infidelity. The method of Levi-Strauss in his Structural Study of Mythology was used in analyzing the structures of each of the six films. The data of this study were gathered through watching the six films from October 2013 to January 2014. The researcher looked on the structure of the story and the characters. Results showed that structuring an infidelity-themed movie, Pursue, Stop, Conflict, Reconcile, Unaware, Revealed Truth, Meeting and Parting subthemes comprise these films. The common and most numbered in a column, in terms of number in action a character does: the Pursue, Conflict, and Parting themes. Revealed Truth, Unaware, Stop, reconcile, and Meeting themes interchanged in their positions of being the next most numbered column depending on the plot of the film. The legal wives or girlfriends were presented as the ones who fought for what should belong to them. The legal husbands or boyfriends they could be to their partners. They did not start a fight but when they saw their loved ones being with another man, they would attack the other man. The legal husbands or boyfriends who were being torn between two women gave in to temptation but later escaped from it and fixed the problem. The mistresses or the third party partners are presented as the aggressive type. As shown in the movies, to be a mistress or to have a mistress makes life complicated. A mistress or the one who has a mistress struggles in trying to fight for something but usually ends up losing, not having what she wanted. Moreover, the third party brings destruction to the relationship and family of the legally married person he/she is involved with, having more lies and mistakes piled up, that have affected the people around him/her.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts